The UPCA Integrated Graduate Program - Architecture, UP College of (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment, 2025)
The Integrated Graduate Program (IGP) provides a collaborative and interdisciplinary learning environment through the offering of flexible curricula. These allow entry points for all fields of expertise and dynamic courses that tackle emergent issues to undertake cutting-edge research in the Designed and Built Environments.